2015
DOI: 10.1097/md.0000000000001783
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors Increase the Risks of Diabetic Peripheral Neuropathy in Patients With Type 2 Diabetes Mellitus

Abstract: This study aimed to examine whether poor glycemic control, measured by glycated hemoglobin A1C (HbA1c) and other cardiovascular risk factors, can predict diabetic peripheral neuropathy (DPN) in patients with type 2 diabetes mellitus (DM).Patients aged ≥30 years with type 2 DM, enrolled in the National Diabetes Care Management Program, and free of DPN (n = 37,375) in the period 2002 to 2004 were included and followed up until 2011. The related factors were analyzed using Cox proportional hazards regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 44 publications
8
39
1
Order By: Relevance
“…Similarly, microalbuminuria (p=0.0118, OR=1.01), urinary creatinine (p=0.0462, OR=1.00) were found to be significant risk factor where HbA1c (p=0.0077, OR=1.72) was found to be the most significant predicting risk factor for DPN complication of type 2 diabetes in Bangladesh. It is consistent with other finding that age and diabetic duration is insignificant [15,[43][44][45][46][47][48] here since all the patients are more than 40 years of age and the diabetic duration is minimum of 10 years.…”
Section: Dpnsupporting
confidence: 92%
“…Similarly, microalbuminuria (p=0.0118, OR=1.01), urinary creatinine (p=0.0462, OR=1.00) were found to be significant risk factor where HbA1c (p=0.0077, OR=1.72) was found to be the most significant predicting risk factor for DPN complication of type 2 diabetes in Bangladesh. It is consistent with other finding that age and diabetic duration is insignificant [15,[43][44][45][46][47][48] here since all the patients are more than 40 years of age and the diabetic duration is minimum of 10 years.…”
Section: Dpnsupporting
confidence: 92%
“…The association of elevated levels of triglycerides with DPN has also been evaluated in subjects with T1DM (40) and T2DM (41, 45, 47, 48). In a study of patients with mild to moderate diabetes, a correlation between the loss of myelinated fiber density and hypertriglyceridemia was observed, independent of disease duration, age, diabetes control, or other variables (49), suggesting an important influence of elevated triglycerides on the progression of DPN.…”
Section: Individual Mets Components and Dpnmentioning
confidence: 99%
“…In the present study, in vitro and in vivo experiments were performed which demonstrated that YWHAB had a significant role in neointimal hyperplasia by enhancing the migration of VSMCs following carotid artery injury. Patients with T2DM have a high risk for vascular restenosis following endovascular interventional therapy (4,25,26). Imbalanced caloric intake is the major cause of T2dM, and previous data have indicated that excessive plasma FFA levels induced by a high fat intake are responsible for this pathological change (27).…”
Section: Discussionmentioning
confidence: 99%